The importance of surface layer parameterization in modeling of stable atmospheric boundary layers. (18th August 2014) - Tastula, Esa‐Matti; Galperin, Boris; Sukoriansky, Semion; Luhar, Ashok; Anderson, Phil
Abstract The accuracy of prediction of stable atmospheric boundary layers depends on the parameterization of the surface layer which is usually derived from the Monin–Obukhov similarity theory. In this article, several surface‐layer models in the format of velocity and potential temperature Deacon numbers are compared with observations from CASES99, Cardington, and Halley datasets. The comparisons were hindered by a large amount of scatter within and among datasets. Tests utilizing R2 demonstrated that the quasi‐normal scale elimination (QNSE) theory exhibits the best overall performance. Further proof of this was provided by 1D simulations with the Weather Research and Forecasting (WRF) model.